A Review of Educational Progress and Reform in the District Primary Education Program (Phases I and II) - World Bank (Washington, DC, 2014)
The District Primary Education Program (DPEP) is a centrally sponsored scheme launched by the Government of India in partnership with the state governments and external donor agencies seeking to expand the opportunities for poor and disadvantage children to receive quality primary education. This report assesses the progress made in terms of outcomes and processes in the first two DPEP programs. The report contains an introduction, chapters on assessment of the progress toward outcomes and the status and effectiveness of DPEP interventions, and a conclusion.